Fabrication and solar modulation of thermochromic hydrogel for smart window application - Zhou, Yang (2019)
In the past half decades, hydrogels have received increasing attention, due to their exceptional wide range of promising applications such as drug delivery, sensing, and tissue engineering, etc. A large number of hydrogel products are sensitive to environmental stimuli, such as temperature, pH, etc. Due to the intrinsic properties, different thermos-responsive hydrogels have been fabricated and developed for energy saving smart windows.